1965
DOI: 10.1042/bj0960607
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the pentose cycle in the perfused cow's udder

Abstract: 1. The distributions of (14)C have been compared in the glucose and galactose moieties of lactose obtained from cows' udders perfused with blood containing [1-(14)C]-, [2-(14)C]- and [6-(14)C]-glucose. The (14)C of the glucose moiety was found in the same position as that of the administered glucose, but in the galactose moiety the (14)C from [2-(14)C]glucose was extensively randomized into positions 1 and 3. It is concluded that the glucose moiety arose from free glucose and the galactose moiety from hexose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…The calculated percentage of metabolism of glucose 6-phosphate pool to galactose moiety of lactose during early lactation was about 92% in 87.5%HF cattle and 80% in 50%HF cattle (Chaiyabutr et al 2000c). The percentages of these values were consistent with the results reported in normally fed goats and bos Taurus cows (Wood et al, 1965;Linzell, 1968). During lactation advance to late lactation, the percentages of these values decreased markedly in 87.5%HF cattle.…”
Section: Recycling = (T3-t14)×100/t3supporting
confidence: 81%
“…The calculated percentage of metabolism of glucose 6-phosphate pool to galactose moiety of lactose during early lactation was about 92% in 87.5%HF cattle and 80% in 50%HF cattle (Chaiyabutr et al 2000c). The percentages of these values were consistent with the results reported in normally fed goats and bos Taurus cows (Wood et al, 1965;Linzell, 1968). During lactation advance to late lactation, the percentages of these values decreased markedly in 87.5%HF cattle.…”
Section: Recycling = (T3-t14)×100/t3supporting
confidence: 81%
“…These results agree with prolonged treatment of rbST in crossbred HF cows, which percentage of glucose 6-phosphate metabolized via the pentose phosphate pathway were variable in different stages of lactation (Chaiyabutr et al, 2008b). However, these findings differed to those studies in the isolated perfused udder of cow by Wood et al (1965), in which about 23-30% of the glucose was metabolized via the pentose phosphate pathway. It is probable that no consideration of the recycling of glucose 6-phosphate metabolized via the pentose cycle in the udder with the consequent loss of 3 H from glucose 6-phosphate (Davis and Bauman, 1974).…”
Section: Discussionsupporting
confidence: 56%
“…The concentration of milk lactose was determined by spectrophotometry (Teles et al, 1978). Lactose radioactivity was determined after isolation by the hydrolysis method (Wood et al, 1965). Milk fatty acids was extracted from 1 ml of an aliquot thawed milk in 2 mL of Dole's solution (Dole, 1956), (iso-propanol 40: n-heptane 10: 1N H 2 SO 4 1, v/v) shaking in water bath for 30 min.…”
Section: Chemical Methods: Radiochemicals For [U-mentioning
confidence: 99%
“…They further compared the distributions of 14 C in the glucose and galactose moieties of milk lactose from cows' udders perfused with blood containing [1-14 C]-, [2-14 C]-, and [6-14 C]glucose. On the basis of these data, they concluded that the glucose moiety primarily arose from free glucose but that the galactose came, in part, from hexose phosphate intermediates as a result of the pentose phosphate pathway activity (33). They estimated the proportional glucose utilization in the mammary gland: 1) 20 -30% via the pentose cycle, 2) ϳ10% by the Embden-Meyerhof pathway, and 3) 60 -70% converted into lactose (33).…”
Section: Low-carbohydrate/high-fat Dietmentioning
confidence: 99%